Implementation of Active Learning Method in Fiqh Learning (Case Study at Ma’had Aly Lirboyo Kediri) - Maulana, Muhammad Haris; Reza Ahmad Zahid; Sri Susanti Tjahja Dini (Journal of Research in Islamic Education, 2024)
The use of appropriate learning methods is a key factor in the teaching and learning process. Success in mastering a range of competencies is a primary goal for students. Active learning, as a teaching method, can enhance the critical thinking skills of students, thereby facilitating a deeper understanding of the material being taught. This research employs a qualitative approach, using descriptive and case study methods, to generate in-depth descriptive data in the form of words or oral expressions from individuals, groups, or situations. The study draws conclusions based on three aspects: planning, implementation, and evaluation.First, planning is focused on a simplified syllabus. Second, in the implementation phase, lecturers employ active learning techniques, including active debates, direct instruction, and small group discussions. Third, evaluation/assessment conducted by lecturers encompasses cognitive, psychomotor, and affective domains.